Ya’juj dan Ma’juj dan Hubungannya dengan Dunia Modern: Telaah atas Penafsiran Imran Hosein dalam An Islamic View of Gog and Magog in the Modern World - Sirajuddin Bariqi (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2020)
Imran Hosein is a sufi-interpreter who is concerned about the study of Gog and Magog. His interpretation combines external(zahir) and internal (batin)knowledge. From this, he produced interpretation out of the mainstream Muslim thought. His interpretation is summarized in the book An Islamic View of Gog and Magog in the Modern World. He viewed that Gog and Magog had long come out. They were the Khazars of the Caucacus Mountains and afterwards divided into Anglo-American-Israeli Alliance (Gog) and modern Russia (Magog). They are the ones behind the corrupt, disruptive, and godless modern world system. This paper analyzes Imran Hosein interpretation of Gog and Magog and its relationship with the modern world. Furthermore, the author also tests the validity of his interpretation based on, (a) the factors behind the interpretation, and (b) the extend to which the possible interpretation when viewed from the rules of usūl al-tafsīr. The result of this study concludes that there are inconsistencies in the use of the methodology used by Imran Hosein and injustifices in using interpretive sources. This makes the product of the interpretation non-scientific.